Magnetic Resonance Angiography Determined Sex-Related Variations in Configuration of Entire Circle of Willis in Bengali Population of Chattogram Division - Hashem, Jehan; Ur Rahman, Imtiaz; Bhowmick, Baishakhi; Reza, Rumela; Sohel, Ibrahim; Fatema, Sharmin (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2025)
Background: Magnetic Resonance Angiography (MRA) is a group of techniques based on Magnetic Resonance Imaging (MRI) for imaging of blood vessels. It’s the most widely used method for detecting the morphology of Circle of Willis (COW). By using the 3D-TOF-MRA the present study was aimed to evaluate the anatomical variations in the Circle of Willis between male and female in Bengali population of Chattogram division. Materials and methods: This cross-sectional observational study was conducted in the Department of Anatomy, Chittagong Medical College, Chattogram, upon 60 study subjects (29 were male & 31 were female) by dividing them intotwo groups (£40 years and >40 years of age). For statistical analysis unpaired student’s t-test was done and p-value was considered significant if it was <0.05 at 95% level of confidence. Results: The participant's age range was between 02 -76 years with a mean ± SD age of 35.20±18.25 years. The entire Circle of Willis (COW) variations were evaluated by 3D TOF MRA between male and female. The most common configuration in both sexes was partially complete Circle of Willis (COW). On comparing the prevalence of individual configuration of COW among the gender, no significant difference was observed. Conclusion: Results of the present study provides some baseline data upon which further studies can be performed by other investigators in this field. These findings might also be helpful during the surgery at the skull base. Chatt Maa Shi Hosp Med Coll J; Vol.23 (2); July 2024; Page 29-33